2012
DOI: 10.4172/2161-0525.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Contaminants on the Testes of Oreochromis niloticus with Special Reference to Ultrastructure of Spermatozoa in Lake Manzala (Egypt)

Abstract: IntroductionThe importance of Nile tilapia, Oreochromis niloticus in aqua cultures is due to its spreading in most countries of the world [1]. It breads in captivity and wide variety of water conditions [2]. Lake Manzalah (LM) is one of the most important lakes in Egypt that provides more than 70% of the total fishery of the country [3] and considered as a highly polluted with toxic heavy metals and pesticides due to progressive increase of industrial and agricultural drainage, as well as sewage out fall from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…In the present study, testis shows the vaccuolation, structural changes in the germ cells such as sickle shaped germ cells and the rupturing of the germ cells. Similar observations were made by the Shalaby and Migeed, (2012) where they studied the impact of environmental contaminant on the testis of Oreochromis niloticus. Kumar et al, (2007) also reported the presence of large number of inter and intra tubular vacuoles, condensation of spermatogonic cells in the testis of Heteropneustus fossilis after exposure of liner alkyl benzene sulphonate.…”
Section: Resultssupporting
confidence: 73%
“…In the present study, testis shows the vaccuolation, structural changes in the germ cells such as sickle shaped germ cells and the rupturing of the germ cells. Similar observations were made by the Shalaby and Migeed, (2012) where they studied the impact of environmental contaminant on the testis of Oreochromis niloticus. Kumar et al, (2007) also reported the presence of large number of inter and intra tubular vacuoles, condensation of spermatogonic cells in the testis of Heteropneustus fossilis after exposure of liner alkyl benzene sulphonate.…”
Section: Resultssupporting
confidence: 73%
“…The seasonal investigations of both females and males GSI organized as the highest values were in spring, followed by summer, while the lowest female GSI values were in winter, and in autumn for males. Such results are in accordance with those of many studies (Njiru et al, 2006;Shalaby & Migeed, 2012;Hamed et al, 2016;Khallaf et al, 2020). This study also agrees with El-Kasheif et al (2013) and Khallaf et al (2020) concerning the fact that the female Nile tilapia individuals have higher value of GSI than males at constant age, length and season; besides, the seasonal variations of both O. niloticus sexes following nearly the same trend.…”
Section: Discussionsupporting
confidence: 93%
“…Necrosis has been characterized as passive, accidental cell death resulting from environmental perturbations or as a well‐regulated process activated by rather specific physiological and pathological stimuli (Proskuryakov, ). Many studies have shown that several factors, for example, pollution and heavy metals, induce necrotic changes in the testes of fish (Shalaby & Migeed, ) and mammals (Niknafs et al., ). In this process, characteristic nucleus changes, defined as pyknosis, are commonly observed and include nucleus contraction and chromatin condensation.…”
Section: Discussionmentioning
confidence: 99%